Weberian and Anti-Weberian Discourse: To the Question of the Hypnotic Power of Classics on the Example of “Protestant Ethics” - Dmitry Kataev (Journal of Economic Sociology, 2018)
The article is a response to the text by R. I. Kapelyushnikov, “Weber’s Hypnosis: Notes on ‘Protestant Ethics and the Spirit of Capitalism.’” The reasons and main directions of criticism and anti-criticism of the “Weber thesis,” about the emergence of capitalism due to Protestant ethics, are considered. In light of the criticisms of a well-known domestic economist, the Weberian and anti-Weberian dispute has been analyzed around one of the most cited classics, which testifies to the heuristic value of Max Weber’s scientific heritage, which remains relevant today. It should be noted that the 100-year narrative (the first critics of the Protestant thesis appear immediately after the publication of the Protestant ethic) requires more detailed research. Interpretation of Max Weber’s creativity is possible only in the context of the complete collection of works (Max. Weber-Gesamtausgabe [1984–2017]), including the systematics of the sociology of religion (which included “Protestant Ethics”) and, later, the 7-volume edition of “Economics and Society” on the economic ethics of world religions. The uncharted and authentic reflection of the legacy of the classic is possible only in view of a holistic reading of the classic, taking into account the historical, biographical, contextual (in the case of Weber’s theoretical discussions in the methodological dispute and controversy with the materialist understanding of history), categorical-conceptual, and methodological aspects, as well as the receptive and actualizing components. As a refutation of the criticism of the well-known economist, arguments are also presented in favor of W. Schluchter’s “Weberian research program” and the reconstructed paradigm of T. Schwinn and G. Albert. As a conclusion, the main lines of actualizing the legacy of the classic, which originates in the “Protestant Ethics,” are highlighted.